The Role of the Prosecutor’s Office in Promoting Restorative Justice for Social Reintegration and Prevention of Recidivism - Sitorus, Neeysha Nathani; Simamora, Janpatar (Jurnal Indonesia Sosial Sains, 2025)
This study examines the role of the Prosecutor’s Office in promoting the implementation of Restorative Justice as an effort to achieve social reintegration and prevent recidivism in Indonesia. The conventional retributive criminal justice system is considered less effective in restoring relationships between offenders, victims, and the community. As an alternative, restorative justice emphasizes reconciliation and social healing. Through Regulation of the Attorney General of the Republic of Indonesia No. 15 of 2020, prosecutors are authorized to terminate prosecution based on restorative justice principles. Its implementation is reflected in the increasing number of cases resolved through peaceful agreements and the establishment of Restorative Justice Houses across regions. However, challenges such as potential misuse, limited resources, and legal culture resistance remain. Nevertheless, the Prosecutor’s Office continues to strengthen its role through prosecutor training, tiered supervision, and inter-agency collaboration to ensure justice that is accountable, humanistic, and oriented toward social restoration.